Effect of maternal chronic disease on obstetric complications in twin pregnancies in a U.S. cohort - Werder, Emily (2013)
OBJECTIVE: To evaluate the effect of maternal chronic disease on obstetric complications among twin pregnancies. DESIGN: Multicenter retrospective observational study. SETTING: The 12 Consortium on Safe Labor (CSL) clinical centers (19 hospitals). PATIENT(S): Twin pregnancies (n=4,821) delivered ≥ 23 weeks of gestation and classified by maternal chronic disease (either none or any of the following: asthma, depression, hypertension, diabetes, and heart, thyroid, gastrointestinal or renal disease). INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): Gestational age at delivery, gestational hypertension, preeclampsia, gestational diabetes, placental abruption, placenta previa, hemorrhage, chorioamnionitis, maternal postpartum fever, premature rupture of membranes, labor onset (spontaneous versus nonspontaneous), route of delivery, and maternal admission to intensive care unit. RESULT(S): Women with chronic disease delivered earlier (mean gestational length, 34.1 vs. 34.6 weeks, p<0.0001) and were less likely to have term birth (risk ratio (RR): 0.80; 95% confidence interval (95% CI): 0.70-0.90). Cesarean delivery after spontaneous labor (RR: 1.20; 95% CI: 1.05-1.37) was also increased with chronic disease. No statistically significant effects were observed for other complications studied. Women who used ART were more likely to hemorrhage, independent of chronic disease, but other findings were generally similar to the non-ART sample. CONCLUSION(S): Chronic disease was associated with additional risk of earlier delivery and cesarean section after spontaneous labor in a nationwide sample of US twin pregnancies. CAPSULE: Among twin pregnancies, maternal chronic disease was associated with additional risk of earlier delivery and cesarean section after spontaneous labor, but not with other obstetric complications.